2016
DOI: 10.1021/acs.oprd.6b00101
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Photocatalysis: A Microreview of Visible Light Mediated Ruthenium and Iridium Catalyzed Organic Transformations

Abstract: Photocatalytic organic transformations utilizing ruthenium and iridium complexes have garnered significant attention due to the access they provide to new synthetic spaces through new reaction mechanisms. A survey of the photophysical data and the diversity of transformations that may be accomplished utilizing commercially available photocatalysts is contained herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
329
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(353 citation statements)
references
References 68 publications
5
329
0
3
Order By: Relevance
“…Die gleiche Gruppe konnte zudem die Vielseitigkeit dieses Aktivierungsmodus durch Kombination mit einer C-F-Alkenylierung zeigen. [68] Inspiriert durch den Sehzyklus von Säugetieren entwickelte diese Gruppe eine kontra-thermodynamische Isomerisierung polarisierter Alkene,k atalysiert durch (À)-Riboflavin (Vitamin B 2 ). [69]…”
Section: Geometrische E!z-isomerisierungunclassified
“…Die gleiche Gruppe konnte zudem die Vielseitigkeit dieses Aktivierungsmodus durch Kombination mit einer C-F-Alkenylierung zeigen. [68] Inspiriert durch den Sehzyklus von Säugetieren entwickelte diese Gruppe eine kontra-thermodynamische Isomerisierung polarisierter Alkene,k atalysiert durch (À)-Riboflavin (Vitamin B 2 ). [69]…”
Section: Geometrische E!z-isomerisierungunclassified
“…These results seemed logical considering that Ir(ppy) 3 is the only photocatalyst with an excited state oxidation potential ( E 1/2 Ir 4+ /Ir* 3+ =−1.73 V) sufficient for the direct reduction of phthalimide 4 ( E red =−1.57 V vs. SCE, see SI) 16. We also found that inexpensive organic photocatalysts 4CzIPN and 2CzPN both showed quenching in presence of protonated isoquinoline, while no quenching was observed with isoquinoline alone 18.…”
mentioning
confidence: 94%
“…We chose to investigate the Ir(ppy) 3 ‐catalyzed photocatalytic decarboxylation of α,β‐unsaturated carboxylic acids, a reaction developed in our laboratory (Scheme 5 A) 15. By comparing the excited state potentials of Ir(ppy) 3 ( E 1/2 Ir 4+ /Ir* 3+ =−1.73 V and E 1/2 Ir* 3+ /Ir 2+ =0.31 V vs. SCE) with the reduction potentials of BrCF 2 COOEt ( E red =−0.57 V vs. SCE, see SI) and cinnamic acid ( E red =−1.09 V vs. SCE, see SI), we reasoned that the reaction would most likely proceed through the oxidative quenching of the fluorinating agent, thus generating the CF 2 COOEt radical of interest 16. Nevertheless, due to the extremely high excited state oxidation potential of Ir(ppy) 3 , we were curious to probe whether the reduction of cinnamic acid, albeit unexpected, could take place (Scheme 5 B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Of which, visible-light-mediated E!Z isomerization of simple alkenes can be achieved by using photosensitizers as a safe and clean energy source (Scheme 1b). [14] This approach has significant appeal both in terms of atom economy and environmentally benign nature.I nr ecent years, photocatalysts such as iridium-base triplet photosensitisers, [15] organic dyes such as riboflavin, [16] aromatic keto compounds such as 2-iodo-9-fluorenone, [17] and covalent organic frameworks (COF) [18] have been employed to promote the E to Z isomerization of alkenes (Scheme 1b). Detailed investigations by Weaver,R ueping, Gilmour,W ang, Balaraman and others, carefully delineated the sensitized isomerization mechanisms and deliveredt he E to Z isomerization of stilbenes, [15b, 17, 18] allylamines, [15a] a,b-unsaturatede sters, [15d, 16a] cinnamonitriles, [16c] allylic alcohols, [19] styrenyl boron species [15f] andv inyl silanes.…”
mentioning
confidence: 99%